Predictability of seasonal mood fluctuations based on perceptions of weather conditions among residents in Iceland : the relationship between perceptions of weather conditions and seasonality - Harpa Hlín Gunnarsdóttir 1981- (2024)
Previous research has revealed that weather influences mood and energy. However, thus far, no study explored the effects of weather on mood in relations to seasonality and seasonal affective disorder in Iceland. Main purpose of this thesis was to analyze the association between subjective perceptions of weather conditions and experiences of seasonal changes in well-being in Iceland. Based on prior research work it was hypothesized that cloudy, cold, and sunny weather will highly correlate with seasonality. Data from an epidemiological study, the EPiC SAD study, with a random sample from the national registry (N= 1977) was analyzed to test if subjective perceptions of weather, measured with the Seasonal Pattern Assessment Questionnaire (SPAQ), could predict seasonality group of participants. Results of a binary logistic regression indicated that there was a significant association between the SPAQ weather items and the classification into seasonality and non-seasonality group (p<.001). Cold weather (p<.001) and short day (p<.001) were significant predictors in the model whereas warm, rainy, sunny, dry, cloudy, and windy weather as well as long day were not significant. Moreover, cold weather and short day are weather conditions related to the winter in Iceland. Cold weather has also been related to less frequent physical activity. Thus, physical activity during winter could possibly assist in the reduction of seasonality symptoms. Further analysis revealed that younger participants and women in the sample were more likely to score high on seasonality than older participants and men. Future study could explore if those variables are moderators in the regression model. The present study is the first to focus on the relationship between the weather subscale of SPAQ and seasonality in Iceland. Results of the study highlight the important role in different weather perceptions especially in people at risk of seasonal affective disorder. Rannsóknir hafa sýnt að veður hefur áhrif á lundarfar og atorku. Hins ...